A preparation method for forming silicon dioxide core-shell nanomaterial on the surface of silver nanospheres
By forming a silicon dioxide core-shell layer on the surface of the silver nanosphere and self-assembly on the conductive polymer film, reversible regulation of the resonance properties of the local surface of the silver nanosphere is achieved, and the static and irreversible problems of the regulation methods in the prior art are solved, and efficient reversible regulation and large-scale production are achieved.
Patent Information
- Application Number
- CN202410873212.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-07-01
AI Technical Summary
The silver nanosphere regulation method in the prior art is static and irreversible, making it difficult to achieve reversible regulation of the resonance properties of its local surface plasmon.
By forming a core-shell layer of silica on the surface of the silver nanospheres and self-assembly on the conductive polymer film, the surrounding environmental media around the silver nanospheres/silica is regulated by changing the dielectric parameters of the conductive polymer, thereby achieving reversible regulation of the local surface plasmon resonance properties.
Reversible regulation of the resonance properties of the local surface of silver nanospheres is achieved, and the problem of static and irreversible regulation methods in the prior art is solved, and the synthesis method is simple and can be produced on a large scale.
Smart Images

Figure CN118754460B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanocomposite materials, and in particular to a method for preparing a silicon dioxide core-shell nanomaterial formed on the surface of a silver nanosphere. Background Art
[0002] Silver nanospheres are a kind of precious metal nanomaterial that has attracted much attention in recent years. Due to their unique localized surface plasmon resonance properties, silver nanospheres have shown broad application prospects in the fields of nanobiology, catalysis, optics and electricity. The localized surface plasmon resonance properties depend on the size and shape of the silver nanospheres. Silver nanospheres of different diameters absorb and scatter light differently, and then show localized surface plasmon resonance absorption peaks of different wavelengths. In addition, the dielectric properties of the surrounding medium of the silver nanospheres will also affect their surface plasmon properties. At present, the localized surface plasmon resonance properties of silver nanospheres are mainly regulated by changing their composition, shape and size. However, the above regulation method is static and irreversible. Once the composition, shape and size of the silver nanosphere are determined, its plasmon shape is determined accordingly. Therefore, the reversible regulation of the localized surface plasmon resonance properties of the silver nanospheres is achieved by changing the surrounding medium of the silver nanospheres to meet the needs of practical applications. Due to the active chemical properties of the surface of the silver nanospheres, the method of adding an inert passivation layer to the surface of the silver nanospheres is adopted to protect them. Summary of the invention
[0003] In order to solve the above problems, the purpose of the present invention is to provide a preparation method of silica core-shell nanomaterials formed on the surface of silver nanospheres, solve the static and irreversible technical problems of the silver nanosphere regulation method in the prior art, change the surrounding environment medium of the silver nanospheres / silicon dioxide to achieve reversible regulation of its localized surface plasmon resonance properties, the synthesis method is simple, and can be produced on a large scale in practical applications.
[0004] In order to achieve the above object, the technical solution of the present invention is as follows:
[0005] The present invention provides a method for preparing a silicon dioxide core-shell nanomaterial formed on the surface of a silver nanosphere, comprising the following steps:
[0006] S1. Centrifuging and re-dispersing the silver nanosphere dispersion;
[0007] S2. Anhydrous ethanol, deionized water and ethyl orthosilicate solution were added to the above dispersion and stirred for 30 mins;
[0008] S3. A certain amount of ammonia water was added to the above solution and stirred for 15 h to obtain silica-coated silver nanospheres;
[0009] S4. After centrifuging the solution in S3, discard the supernatant, wash 3-4 times, and finally disperse the silica-coated silver nanospheres into 20 mL of deionized water and store at 4°C for use;
[0010] S5. Electrodeposition of a conductive polymer film on conductive glass;
[0011] S6. The silica core-shell nanomaterial formed on the surface of the silver nanospheres is self-assembled on the conductive glass deposited with the conductive polymer, and finally the silica core-shell nanomaterial formed on the surface of the silver nanospheres with controllable thickness on the conductive polymer is obtained.
[0012] Furthermore, the S1 comprises the following steps:
[0013] S11. Take 4 mL of a dispersion of silver nanospheres with a diameter of 60 nm and centrifuge at a centrifuge speed of 8000 rpm for 15 mins;
[0014] S12. After removing the supernatant by centrifugation, disperse it in 0.3 mL of deionized water for later use.
[0015] Furthermore, in the S2, the anhydrous ethanol is 5 ml, the deionized water is 0.175 ml, the tetraethyl orthosilicate is 0.05 mL, the concentration of the tetraethyl orthosilicate is 1.25%, the stirring speed is 400 rpm, and the stirring time is 30 minutes.
[0016] Furthermore, the ammonia water in S3 is 0.05 mL, the stirring speed is 400 rpm, and the stirring time is 15 h.
[0017] Further, the S4 comprises the following steps:
[0018] S41. After centrifuging the solution in S3, discard the supernatant, centrifuge at 15000 rpm for 6 mins, and wash repeatedly 3-4 times with anhydrous ethanol and deionized water in a ratio of 1:1 to remove unreacted ethyl orthosilicate and ammonia;
[0019] S42. Disperse the silver nanospheres / silicon dioxide in 20 mL of deionized water and store at 4°C until use.
[0020] Furthermore, the conductive glass in S5 is ITO or FTO, the voltage setting range of the electrodeposited conductive polymer film is -0.2V-1.05V, and the conductive polymer is polyaniline or polypyrrole or poly (3,4-ethylenedioxythiophene) high molecular conductive polymer.
[0021] Further, the S6 comprises the following steps:
[0022] S61. Take 1-2 mL of the silica-coated silver nanosphere dispersion and centrifuge to remove the supernatant. The centrifugal speed is 15000 rpm and the centrifugal time is 6 mins;
[0023] S62. The conductive glass ITO or FTO deposited with the conductive polymer is used as a substrate and fixed on a precision electric displacement platform, and 20-40 μL of the centrifuged silica-coated silver nanosphere solution is dropped on the surface of the substrate;
[0024] S63. A fixed fluorosilanized hydrophobic glass plate is fixedly placed 300 μm above the liquid, and is moved through the above-mentioned precision electric displacement platform at a constant speed of 1 μm / s, forming a liquid meniscus at one edge, and then dragging it over the substrate to gather and coat the nanoparticles, and the nanoparticles are transported by evaporation-induced convection;
[0025] S64. After the surface of the nanoparticles is naturally dried, a silica core-shell nanomaterial with a controllable thickness formed on the surface of silver nanospheres on the conductive polymer can be obtained.
[0026] By adopting the above technical solution, the present invention has the following advantages:
[0027] The invention provides a preparation method of a silicon dioxide core-shell nanomaterial formed on the surface of a silver nanosphere, wherein a silicon dioxide shell layer is formed on the surface of the silver nanosphere as a passivation layer to protect the silver nanosphere from oxidation. At the same time, the silver nanosphere / silicon dioxide core-shell nanomaterial is self-assembled on an ITO or FTO conductive glass deposited with a conductive polymer, and the dielectric parameters of the conductive polymer are changed by changing the voltage, thereby changing the surrounding medium of the silver nanosphere / silicon dioxide to achieve reversible regulation of its localized surface plasmon resonance properties. The synthesis method of the invention is simple and can be mass-produced in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 TEM image of the sample of Example 1 of the present invention;
[0029] Figure 2 TEM image of the sample of Example 2 of the present invention;
[0030] Figure 3 The cyclic voltammetry curve of the polyaniline film deposited on the conductive glass ITO in Example 3 of the present invention;
[0031] Figure 4 Schematic diagram of electrical regulation of the sample structure of Example 4 of the present invention;
[0032] Figure 5 It is a schematic diagram of the self-assembly process of the sample of Example 4 of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is described in detail below in conjunction with the drawings in the specification. It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0034] The present invention provides a method for preparing a silicon dioxide core-shell nanomaterial formed on the surface of a silver nanosphere, comprising the following steps:
[0035] S1. Centrifuging and re-dispersing the silver nanosphere dispersion;
[0036] S1 includes the following steps:
[0037] S11. Take 4 mL of a dispersion of silver nanospheres with a diameter of 60 nm and centrifuge at a centrifuge speed of 8000 rpm for 15 mins;
[0038] S12. After removing the supernatant by centrifugation, disperse it in 0.3 mL of deionized water for later use.
[0039] S2. Add anhydrous ethanol, deionized water and tetraethyl orthosilicate solution to the above dispersion and stir for 30 minutes; in S2, anhydrous ethanol is 5 ml, deionized water is 0.175 ml, tetraethyl orthosilicate is 0.05 mL, the concentration of tetraethyl orthosilicate is 1.25%, the stirring speed is 400 rpm, and the stirring time is 30 minutes.
[0040] S3. Add a certain amount of ammonia water to the above solution, and obtain silica-coated silver nanospheres after stirring; S4. Centrifuge the solution in the above S3, discard the supernatant, wash 3-4 times, and finally disperse the silica-coated silver nanospheres into 20mL deionized water and store at 4°C for use; the ammonia water in S3 is 0.05mL, the stirring speed is 400rpm, and the stirring time is 15h.
[0041] S4. After centrifuging the solution in S3, discard the supernatant, wash 3-4 times, and finally disperse the silica-coated silver nanospheres into 20 mL of deionized water and store at 4°C for use;
[0042] S4 includes the following steps:
[0043] S41. After centrifuging the solution in S3, discard the supernatant, centrifuge at 15000 rpm for 6 mins, and wash repeatedly 3-4 times with anhydrous ethanol and deionized water in a ratio of 1:1 to remove unreacted ethyl orthosilicate and ammonia;
[0044] S42. Disperse the silver nanospheres / silicon dioxide in 20 mL of deionized water and store at 4°C until use.
[0045] S5. Electrodepositing a conductive polymer film on the conductive glass; the conductive glass in S5 is ITO or FTO, the voltage setting range of the electrodeposited conductive polymer film is -0.2V-1.05V, and the conductive polymer is a high molecular conductive polymer such as polyaniline, polypyrrole or poly (3,4-ethylenedioxythiophene).
[0046] S6. The silica core-shell nanomaterial formed on the surface of the silver nanospheres is self-assembled on the conductive glass deposited with the conductive polymer, and finally the silica core-shell nanomaterial formed on the surface of the silver nanospheres with controllable thickness on the conductive polymer is obtained.
[0047] S6 includes the following steps:
[0048] S61. Take 1-2 mL of the silica-coated silver nanosphere dispersion and centrifuge to remove the supernatant. The centrifugal speed is 15000 rpm and the centrifugal time is 6 mins;
[0049] S62. The conductive glass ITO or FTO deposited with the conductive polymer is used as a substrate and fixed on a precision electric displacement platform, and 20-40 μL of the centrifuged silica-coated silver nanosphere solution is dropped on the surface of the substrate;
[0050] S63. A fixed fluorosilanized hydrophobic glass plate is fixedly placed about 300 μm above the liquid, and is moved through the above-mentioned precision electric displacement platform at a constant speed of 1 μm / s, forming a liquid meniscus at one edge, and then dragging it over the substrate to gather and coat the nanoparticles, and the nanoparticles are transported by evaporation-induced convection;
[0051] S64. After the surface of the nanoparticles is naturally dried, a silica core-shell nanomaterial with controllable thickness formed on the surface of silver nanospheres on the conductive polymer can be obtained.
[0052] Embodiment 1:
[0053] In this example, silver nanospheres / silicon dioxide core-shell nanomaterials were prepared according to the following steps:
[0054] Take 4mL of silver nanosphere dispersion with a diameter of 60nm, centrifuge at a speed of 8000rpm for 15mins, remove the supernatant and disperse it in 0.3mL deionized water for standby use. Then add 5mL of anhydrous ethanol, 0.175mL of deionized water, and 0.05mL of 1.25% tetraethyl orthosilicate, and stir at a speed of 400rpm for 30mins. Finally, add 0.05mL of ammonia water, stir for 15h at a speed of 400rpm, and finally obtain silica-coated silver nanospheres. Centrifuge the above solution to discard the supernatant, wash repeatedly 3-4 times with anhydrous ethanol and deionized water in a ratio of 1:1 to remove unreacted tetraethyl orthosilicate and ammonia water, centrifuge at a speed of 15000rpm for 6mins, and finally disperse the silver nanospheres / silicon dioxide in 20mL deionized water and store at 4°C for standby use. The synthesized silica shell thickness is 15nm.
[0055] Embodiment 2:
[0056] In this example, silver nanospheres / silicon dioxide core-shell nanomaterials were prepared according to the following steps:
[0057] Take 4mL of silver nanosphere dispersion with a diameter of 60nm, centrifuge at a speed of 8000rpm for 15mins, remove the supernatant and disperse it in 0.3mL deionized water for standby use. Then add 5mL of anhydrous ethanol, 0.175mL of deionized water, and 0.05mL of 1.25% tetraethyl orthosilicate, and stir at a speed of 400rpm for 30mins. Finally, add 0.1mL of ammonia water, stir for 15h at a speed of 400rpm, and finally obtain silica-coated silver nanospheres. Centrifuge the above solution to discard the supernatant, and wash it repeatedly 3-4 times with anhydrous ethanol and deionized water in a ratio of 1:1 to remove unreacted tetraethyl orthosilicate and ammonia water. The centrifugal speed is 15000rpm for 6mins, and finally the silver nanospheres / silicon dioxide are dispersed in 20mL of deionized water and stored at 4°C for standby use. The synthesized silica shell thickness is 30nm.
[0058] Embodiment 3:
[0059] This embodiment prepares the conductive polymer film according to the following steps:
[0060] Polyaniline film was electrochemically deposited in the three-electrode system of the electrochemical workstation. ITO conductive glass was used as the working electrode, platinum mesh was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 20mM aniline was used as the electrolyte. The voltage setting range for electro-deposition of polyaniline film was -0.2V-1.05V, the deposition rate was 20mV / s, the number of cycles was 24, and the thickness of the polyaniline film was 10-15nm.
[0061] Embodiment 4:
[0062] In this embodiment, the thickness-controllable silver nanosphere / silicon dioxide core-shell nanomaterial on the conductive polymer is prepared according to the following steps:
[0063] Take 1-2mL of silver nanosphere / silica dispersion and centrifuge to remove the supernatant, the centrifugal speed is 15000rpm, and the time is 6mins. The conductive glass ITO deposited with polyaniline is fixed on the precision electric displacement platform as the substrate, and 20-40μl of the centrifuged silver nanosphere / silica solution is dropped on the surface of the substrate. In order to accurately limit the liquid during the coating process, a fixed fluorosilanized hydrophobic glass plate is fixed and placed about 300μm above the liquid. By moving the precision electric displacement platform supporting the conductive glass substrate at a constant speed of 1μm / s, a liquid meniscus is formed at the edge of one side, which is then dragged across the substrate to aggregate and coat the nanoparticles, which are transported by evaporation-induced convection. After the surface is dried naturally, a silver nanosphere / silica core-shell nanomaterial with controllable thickness on the conductive polymer can be obtained.
[0064] Experimental results:
[0065] Figure 1 The TEM image of the sample of Example 1 of the present invention is shown. Figure 1 It can be seen that the thickness of the silicon dioxide layer is about 15nm; Figure 2 The TEM image of the sample of Example 2 of the present invention is shown. Figure 2 It can be seen that the thickness of the silicon dioxide layer is about 30nm; Figure 3 The cyclic voltammetry curve of the polyaniline film deposited on the conductive glass ITO in Example 3 of the present invention; the abscissa is the bias voltage applied during deposition, and the ordinate is the current corresponding to the deposition. Figure 4 A schematic diagram of electrical regulation of the sample structure of Example 4 of the present invention is shown, wherein 1 is silver nanospheres, 2 is silicon dioxide, 3 is a conductive polymer layer, 4 is conductive glass ITO, and 5 is applied bias. Figure 5 The schematic diagram of the self-assembly process of the sample in Example 4 of the present invention is shown. Figure 3 , Figure 4 and Figure 5 It can be seen that by changing the voltage, the dielectric parameters of the conductive polymer are changed, thereby changing the surrounding medium of the silver nanospheres / silicon dioxide, and realizing the reversible regulation of the localized surface plasmon resonance properties of the silica core-shell nanomaterials formed on the surface of the silver nanospheres.
[0066] Finally, it should be pointed out that although the present invention has been described with reference to the current specific embodiments, ordinary technicians in this technical field should realize that the above embodiments are only used to illustrate the present invention and are not used as a limitation of the present invention. Various equivalent changes or substitutions can be made without departing from the concept of the present invention. Therefore, as long as the changes and modifications to the above embodiments are within the essential spirit of the present invention, they will fall within the scope of the claims of the present invention.
Claims
1. A method for preparing a silicon dioxide core-shell nanomaterial formed on the surface of silver nanospheres, characterized in that: The following steps are involved: S1. Centrifuging and re-dispersing the silver nanosphere dispersion; S2. Anhydrous ethanol, deionized water and ethyl orthosilicate solution were added to the above dispersion and stirred for 30 mins; In the S2, anhydrous ethanol is 5 ml, deionized water is 0.175 ml, tetraethyl orthosilicate is 0.05 mL, the concentration of tetraethyl orthosilicate is 1.25%, the stirring speed is 400 rpm, and the stirring time is 30 mins; S3. A certain amount of ammonia water was added to the above solution and stirred for 15 h to obtain silica-coated silver nanospheres; The amount of ammonia water in S3 is 0.05 mL, the stirring speed is 400 rpm, and the stirring time is 15 h; S4. After centrifuging the solution in S3, discard the supernatant, wash 3-4 times, and finally disperse the silica-coated silver nanospheres into 20 mL of deionized water and store at 4°C for use; S5. Electrodeposition of a conductive polymer film on conductive glass; The conductive glass in S5 is ITO or FTO, the voltage setting range of the electrodeposited conductive polymer film is -0.2V-1.05V, and the conductive polymer is polyaniline or polypyrrole or poly (3,4-ethylenedioxythiophene) high molecular conductive polymer; S6. self-assembling the silica core-shell nanomaterial formed on the surface of the silver nanospheres on the conductive glass deposited with the conductive polymer, and finally obtaining the silica core-shell nanomaterial formed on the surface of the silver nanospheres with controllable thickness on the conductive polymer; The S6 comprises the following steps: S61. Take 1-2 mL of the silica-coated silver nanosphere dispersion and centrifuge to remove the supernatant. The centrifugal speed is 15000 rpm and the centrifugal time is 6 mins; S62. The conductive glass ITO or FTO deposited with the conductive polymer is used as a substrate and fixed on a precision electric displacement platform, and 20-40 μL of the centrifuged silica-coated silver nanosphere solution is dropped on the surface of the substrate; S63. A fixed fluorosilanized hydrophobic glass plate is fixedly placed 300 μm above the liquid, and is moved through the above-mentioned precision electric displacement platform at a constant speed of 1 μm / s, forming a liquid meniscus at one edge, and then dragging it over the substrate to gather and coat the nanoparticles, and the nanoparticles are transported by evaporation-induced convection; S64. After the surface of the nanoparticles is naturally dried, a silica core-shell nanomaterial with a controllable thickness formed on the surface of silver nanospheres on the conductive polymer can be obtained.
2. The method for preparing a silicon dioxide core-shell nanomaterial formed on the surface of silver nanospheres according to claim 1, characterized in that: The S1 comprises the following steps: S11. Take 4 mL of a dispersion of silver nanospheres with a diameter of 60 nm and centrifuge at a centrifuge speed of 8000 rpm for 15 mins; S12. After removing the supernatant by centrifugation, disperse it in 0.3 mL of deionized water for later use.
3. The method for preparing a silicon dioxide core-shell nanomaterial formed on the surface of silver nanospheres according to claim 1, characterized in that: The S4 comprises the following steps: S41. After centrifuging the solution in S3, discard the supernatant, centrifuge at 15000 rpm for 6 mins, and wash repeatedly 3-4 times with anhydrous ethanol and deionized water in a ratio of 1:1 to remove unreacted ethyl orthosilicate and ammonia; S42. Disperse the silver nanospheres / silicon dioxide in 20 mL of deionized water and store at 4°C until use.